Women's Independence In Henrik Ibsen's The Lady From The Sea Play (1888): A Feminist Approach - Tutiningsih, Tutiningsih; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
The research is proposed to analyze the women's independence which is respresented by the character in Henrik Ibsen's The Lady From The Sea play by Feminist Approach. The research sets two objectives: first is to analyze the play based on the Feminist Approach.This study is qualitative using the play of Henrik Ibsen's The Lady From The Sea play (1888)as the object. There are two kinds of data source: primary and secondary. The primary data source is the play of Henrik Ibsen's The Lady From The Sea and the secondary data source are some literary books and some articles related to the play. The method of collecting data in the research is library research by reading and summarising the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follow: based on feminist approach, women's independence system The Lady From The Sea harm's women's because marginalized and oppresed.